Psychoacoustic Characteristics of Tinnitus versus Temporal Resolution in Subjects with Normal Hearing Sensitivity - Ibraheem, Ola Abdallah; Hassaan, Mohammad Ramadan (International Archives of Otorhinolaryngology, 2017)
Introduction Cochlear or neural mechanisms of tinnitus generation may affect auditory temporal resolution in tinnitus patients even with normal audiometry. Thus, studying the correlation between tinnitus characteristics and auditory temporal resolution in subjects with tinnitus may help in proper modification of tinnitus management strategy.Objective This study aims to examine the relationship between the psychoacoustic measures of tinnitus and the auditory temporal resolution in subjects with normal audiometry.Methods Two normal hearing groups with ages ranging from 20 to 45 years were involved: control group of 15 adults (30 ears) without tinnitus and study group of 15 adults (24 ears) with tinnitus. Subjective scaling of annoyance and sleep disturbance caused by tinnitus, basic audiological evaluation, tinnitus psychoacoustic measures and Gaps in Noise test were performed. Data from both groups were compared using independent sample t-test. Psychoacoustic measures of tinnitus and Gaps in Noise test parameters of the tinnitus group were correlated with Pearson's correlation coefficient.Results Significantly higher hearing threshold, higher approximate threshold and lower correct Gaps in Noise scores were observed in tinnitus ears. There was no significant correlation between psychoacoustic measures of tinnitus and Gaps in Noise test parameters of the tinnitus group.Conclusion Auditory temporal resolution impairment was found in tinnitus patients, which could be attributed to cochlear impairment or altered neural firing within the auditory pathway. It is recommended to include temporal resolution testing in the tinnitus evaluation battery to provide a proper management planning.
Keywords: tinnitus; subjective; auditory processing disorder; auditory pathway disorders; central